Situación afectiva y su relación con la capacidad funcional y cognitiva del adulto mayor institucionalizado y no institucionalizado de la ciudad de Loja - Campoverde Encalada, Maritza Alexandra (2014)
In order to evaluate the relationship between affective state and cognitive and functional capacity of the elderly institutionalized and non-institutionalized Loja City Centers "Daniel Álvarez Sánchez" Social Group and Reina del Cisne "Happy Evenings" , we conducted a qualitative study-descriptive-analytical and prospective, which evaluated 50 adults over these centers. The affective state classification was performed by application of the Geriatric Depression Scale Yesavage, functional capacity: on the basic activities used the Barthel Index and the instrumental activities of Lawton and Brody Index, and to assess the cognitive ability, the Mini-Mental State Examination of Folstein. The results showed that the affective state if it influences cognitive ability in individuals especially refugees, like if there is a relationship to functional capacity, where observe that as affective deterioration increases functional impairment, which is most evident in the instrumental activities of daily living especially in institutionalized patients. So it was concluded that cognitive impairment does not influence the functional capacity for basic activities of daily living for patients as for non-institutionalized institutionalized. But asylum patient’s cognitive deficits if deteriorating influences instrumental activities of daily living. Checking so affective state influences both the functional and cognitive capacity of older adults, the most in the functional capacity of the instrumental activities of older inmates.